(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article offers an in-depth examination of the term "mahāsin" as utilized by al-Qaffāl al-Shāshī. It explores the nuanced implications of this term, elucidating how the scholar employs it to convey the overarching idea that all the commandments within the Sharīʿa are inherently characterized by goodness and beauty.